ANALISIS BIAYA DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MEMBELI ATAU MEMPRODUKSI SENDIRI PADA UD. NABILA JEPARA MEUBEL DAN UD. JEPARA FURNITURE - Simbawa, Astyta Permata; Sondakh, Jullie; Wokas, Heince (ACCOUNTABILITY, 2015)
The situation and current economic conditions impacted the intense competition among the companies of the world. Therefore, the company management needs to create a policy that refers to the creation of the efficiency and effectiveness of the company performance. The management needs the information as a basis for decision making, one of the types of information needed is the management of differential cost analysis information. In this observation, differential cost analysis is used to help management firm in the face of some of the alternatives that exist to make a decision to buy or produce its own by using half-finished wood as a raw material. The purpose of this observation was to analyze the differential costs in the decision to buy or produce own staple at UD Nabila Jepara Furniture and UD Jepara Furniture. The analysis method used in this research is descriptive method. Results of the assessment showed differential costs right a decision has been taken by management of UD Nabila Jepara Furniture and UD Jepara Furniture is producing its own because of differential gain a higher profit than buying from outside.